STRATEGI MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Harbeng Masni (Universitas Batanghari Jambi, 2017)
Abstract : Many factors are often used as a benchmark educational success. One way is to look at the success of the teaching-learning process in achieving its objectives. Another factor that plays an important role at this time is the motivation of the learners in order to prepare himself to initiate a learning process. His relationship with the motivation, it is very often encountered, especially in the scope of the lecture. As there is in fact now a student many reasons to come to the lecture room just to simply fill out the list of attendance or absenteeism. Especially for subjects who according to them are not in line with the course of study they pursue, automatically by themselves they actually underestimate the course. In the course of learning, motivation can be considered as the overall driving force within the students that cause, ensure continuity and provide direction and learning activities, so that the expected objectives can be achieved. Motivation affects the interest in learning a learner because the motivation is the driving force that is in a person to perform certain activities in order to achieve a goal.Keywords: Motivation to Learn